Enhancing Lycopene Biosynthesis in Cereibacter sphaeroides DT.1: Effects of Glutamate and Proline Supplementation and Fermentation Optimization - Yiyan Zhang; Xiongyao Ma; Zhe Xu; Xiangyu Gu; Xiangyang Gu (Fermentation)
Lycopene is a natural carotenoid with antioxidation properties. The objective of the present study was to investigate the roles of glutamate and proline in lycopene biosynthesis in a newly isolated purple non-sulfur bacterium Cereibacter sphaeroides DT.1, under aerobic conditions. This strain contained a distinct CrtI4 capable of converting phytoene to lycopene via four-step desaturation. In order to enhance lycopene production, a crtC knockout mutant was constructed via homologous recombination. Supplementation with glutamate or proline to fermentative medium significantly enhanced intracellular lycopene accumulation in wildtype strain by a respective 99.40 ± 0.54% and 101.70 ± 0.49% and in a ΔcrtC mutant strain by 38.13 ± 0.15% and 39.83 ± 0.27%, respectively. Differential transcriptomic and metabolomic analyses showed that these promoting effects were associated with downregulation of the expression of the acyclic carotenoid 1,2-hydratase gene, and increased accumulation of lycopene precursors such as pyruvate and acetyl-CoA. The fermentation conditions for lycopene production were optimized through shake flask experiments. Feasibility for lycopene production was confirmed in a fed-batch cultivation process and a high yield of 151.10 ± 0.13 mg/L was achieved. This ΔcrtC mutant strain exhibited advantages, such as relatively lower oxygen demand and no need for illumination, making it a potentially useful strain for lycopene production under aerobic conditions.